Jose Rizal ang buhay ng isang bayani - Ateneo de Manila (Quezon City, Philippines). Kagawaran ng Kasaysayan; Bookmark, Inc. (Philippines).
Video documentary on the personal life of Jose Rizal as it is based on the documented evidence obtained entirely from primary sources. It looks at Rizal as a person rather than a public figure. Shows a large collection of photos, letters, and memorabilia.
VHS.
Credits : Narrator, Joonee Gamboa.
Pen Medina as Jose Rizal, Connie Lauigan Chua as Sonya Lolay, Ben Vibar as Ferdinand Blumentritt.
1997 Finalist for Best Documentary Award (Film Academy Awards)
1997 Gawad CCP Pinakamahusay sa Espesyal na Palabas sa Telebisyon.
Keywords: Rizal, Jose -- 1861-1896.; Heroes -- Philippines -- Biography